Pengaruh Luas Lubang Pipa Pada Kolom Pendek Dengan Variasi Diameter Lubang Pipa 1½”, 2”, 2½” Dan 3”. - Agus Sugianto; Andi Marini Indriani; Ismail Husein (Jurnal Teknologi Terpadu, 2015)
AbstractThe use of holes in the manufacture of a column that serves as the placement of sewer commonly found in multi-storey buildings. Understanding of the construction perpetrators of the ideal aperture area of the column need attention so that the ability of the column structure remains fulfilled and a review of functionality also remains accommodated. This research was conducted in the form of short column with concrete cylinder models which were given hole with varied wide then doing test press. The methodology used in this study with the manufacture of concrete cylinder compressive strength of 20 MPa. and variations in the diameter of the pipe hole Ø 1½ ", 2", 2 ½ "and 3" using PVC pipe to mold a hole in the concrete cylinders. Making the hole refers to the standard of making holes in concrete columns up to 4% of the cross sectional area of concrete in accordance with SNI 03 2847 2002. Results of the study provide the conclusion that the ratio between the diameter of the hole Ø 1½ ", 2", 2 ½ "and 3" on the concrete cylinders are any additions to the aperture area of 0.015 cm2 compressive strength decreased by 0.02% against the concrete cylinder diameter of 15 cm and height 30 cm , Making holes in concrete columns resulted in a reduction in compressive strength of concrete. Keywords: wide variation hole, cylinder concrete, short columns. Abstrak Pemakaian lubang dalam pembuatan kolom yang berfungsi sebagai penempatan saluran pembuangan banyak ditemui pada bangunan-bangunan bertingkat. Pemahaman para pelaku konstruksi terhadap luas lubang ideal pada kolom perlu mendapat perhatian agar kemampuan struktur kolom tetap terpenuhi dan tinjauan terhadap fungsi juga tetap terakomodir. Penelitian ini dilakukan pada kolom pendek dengan model berupa silinder beton yang diberi lubang dengan luas bervariasi kemudian dilakukan uji tekan. Metodologi yang dipakai dalam penelitian ini dengan pembuatan silinder beton kuat tekan 20 MPa. Dan variasi diameter lubang pipa Ø 1½”, 2”, 2½” dan 3”  menggunakan pipa PVC untuk cetakan lubang pada silider beton. Pembuatan lubang mengacu pada standar pembuatan lubang pada kolom beton maksimal 4% dari luas penampang beton sesuai dengan SNI 03 2847 2002. Hasil penelitian memberikan kesimpulan bahwa perbandingan antara diameter lubang Ø 1½”, 2”, 2½” dan 3” pada silinder beton adalah setiap penambahan luas lubang 0,015 cm2 terjadi penurunan kuat tekan sebesar 0,02% terhadap silinder beton diameter 15 cm dan tinggi 30 cm. Pembuatan lubang pada kolom beton mengakibatkan terjadinya penurunan kuat tekan beton.Kata kunci : Variasi luas lubang, Silinder beton, kolom pendek.